Association of Physical Activity Levels with Coronary Artery Disease Risk Factors in Middle aged (40-55) Bangladeshi Women (Bangladesh Heart Journal, 2024)
Background: A sedentary lifestyle is associated with increased risk of Coronary Artery Disease (CAD) in women. At least 150min/wk of moderate activity or 75min/wk of vigorous activity or combination is recommended by American Heart Association (AHA) for primary prevention of CAD. The purpose of this study was to assess the physical activity levels of middle aged women and to find out the association of CAD risk factors with physical activity level.Methods: This cross-sectional analytical study was conducted in Dhaka Medical College Hospital (DMCH) cardiology OPD from May 2019 to April 2020. We interviewed 249 middle aged women (40-55) who attended our OPD during the study period and fulfilled the exclusion and inclusion criteria. Global Physical Activity Questionnaire (GPAQ) was used to assess physical activity level. Blood pressure and BMI was measured. OGTT and fasting lipid profile was done. Subjects with low physical activity was assigned in Group I (n=152), moderate activity in group II (n= 93) and high activity in group III (n= 4). Association between the physical activity levels and presence of CAD risk factors like DM, HTN, dyslipidemia and obesity was evaluated. Results: In this study we found that most of the study subjects (61.0%) were in low active group. Overall 70.2% women were menopausal and premature menopause (≤50 years) was found in 47.8% of subjects. Mean age of menopause was 47±3.8; (44-53) years and mean duration of menopause was 3.1±0.5 years. Overall prevalence of DM, HTN, obesity and dyslipidemia was 62.2%, 50.6%, 39.8% and 53.4% accordingly. Women in low active group were having significant higher proportion of DM (52.6%), HTN (65.8%), obesity (57.9%) and dyslipidemia (75.7%) in comparison to moderate active group. Only 4 women were in highly active group and none of the CAD risk factors was present among them.Bangladesh Heart Journal 2024; 39(2): 127-137